PENGELOLAAN HUBUNGAN SEKOLAH DENGAN MASYARAKAT (HUSEMAS) DI SMA NEGERI 1 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Shintia Sabrina (Universitas Negeri Padang, 2014)
This study aimed to determine the management of public school relations in SMA N 1 2X11 Enam Lingkung in sub-province Padang Pariaman. Covering aspects of the planning, actuating, and evaluation which conducted for the management of program’s public school relations. This type of research is descriptive quantitative. Informant selection techniquesin this study using simple random sampling as many as 60 people with research subjects teacher of SMA N 1 2X11 Enam Lingkung. Data collection techniques using quisioner. Results showed generally depicted the management of public school relations in SMA N 1 2X11 Enam Lingkung have a category “good enough” in mean’s score 3,31. Management of school have to be improved public school relations for obtaining result better. Keyword : management, public school relations, management